The Role of Nurses in Addressing Reperfusion Injuries Post-Cardiac Arrest: Pathophysiology, Management, and Prevention - Aishah Ali salem alasmari, Safia Hassan Mohammed Asiri, Njoud Said Alomar, Wafaa Ibrahim Ahmed Morea, Fatima Yahya Ali Asiri, Matoga Abed Salym Al Gorashi, Taghreed Yahya Moh’d Alwadey; Areej Ageely Hassan Abuganan, Norah Mohana Alhabib, Lolwah Abdoh Manea Alasiri, Ghaliah Sultan Almazmomi, Saleh Salman Dubayan Almutairi, Matar Obaid Matar AlMutairi, Wafa Salem Saleh Altamimi, Abdulrahman Munawwikh Alsharari (Journal of International Crisis and Risk Communication Research, 2024)
Cardiac arrest is a critical medical emergency with significant mortality and morbidity rates, exacerbated by the complex phenomenon of reperfusion injuries that occur post-resuscitation. This paper provides an in-depth exploration of the pathophysiological mechanisms underlying reperfusion injuries, including oxidative stress, mitochondrial dysfunction, inflammation, and apoptosis. It highlights the pivotal role of emergency nurses in mitigating these effects through evidence-based practices such as ventilation optimization, coronary intervention, hemodynamic stabilization, temperature control, glucose management, and seizure activity monitoring. Additionally, the paper discusses emerging therapeutic strategies, including the use of cyclosporine, extracorporeal membrane oxygenation (ECMO), and therapeutic hypothermia, while critically evaluating their efficacy based on recent research. By enhancing their understanding of these processes, emergency nurses can effectively contribute to improving patient outcomes in the critical post-cardiac arrest phase.